Design and Synthesis of Fluorescent Methylphenidate Analogues for a FRET‐Based Assay of Synapsin III Binding. (16th June 2020) - Casiraghi, Andrea; Longhena, Francesca; Straniero, Valentina; Faustini, Gaia; Newman, Amy H.; Bellucci, Arianna; Valoti, Ermanno
Abstract: We previously described synapsin III (Syn III) as a synaptic phosphoprotein that controls dopamine release in cooperation with α‐synuclein (aSyn). Moreover, we found that in Parkinson's disease (PD), Syn III also participates in aSyn aggregation and toxicity. Our recent observations point to threo ‐methylphenidate (MPH), a monoamine re‐uptake inhibitor that efficiently counteracts the freezing‐gait characteristic of advanced PD, as a ligand for Syn III. We have designed and synthesised two different fluorescently labelled MPH derivatives, one with Rhodamine Red (RHOD) and one with 5‐carboxytetramethylrhodamine (TAMRA), to be used for assessing MPH binding to Syn III by FRET. TAMRA‐MPH exhibited the ideal characteristics to be used as a FRET acceptor, as it was able to enter into the SK‐N‐SH cells and could interact specifically with human green fluorescent protein (GFP)‐tagged Syn III but not with GFP alone. Moreover, the uptake of TAMRA‐MPH and co‐localization with Syn III was also observed in primary mesencephalic neurons. These findings support that MPH is a Syn III ligand and that TAMRA‐conjugated drug molecules might be valuable tools to study drug‐ligand interactions by FRET or to detect Syn III in cytological and histological samples. Abstract : With ideal GFP‐FRET couple characteristics, TAMRA‐ threo ‐methylphenidate is a promising tool for the study of drug‐ligand interactions. We designed and synthetized this fluorescent conjugate and assessed its ability to interact with human Synapsin III, a synaptic partner of α‐synuclein co‐participating in Parkinson's disease pathology, by FRET.